Factors influencing the implementation of parenting plans in South Africa - Prinsloo, Christina Elizabeth (University of Pretoria, 2018)
Divorce is one of the most traumatic experiences that families and children can encounter. Many children are exposed to the distress related to it. In South Africa, the Children’s Act 38 of 2005 section 33(1) attempts to implement a model for co-parenting with parenting plans that describe how the parents will contribute to the care and well-being of their child or children. Although parenting plans are included in mediation processes, the implementation thereof is not always successful and in the best interests of the children involved. In this research study, the researcher aimed to explore divorced parents’ experiences of factors that influence the implementation of the parenting plans. The views of professionals involved in intervention with divorce regarding the factors that influence the implementation of parenting plans, were also explored. The theoretical framework for this study was the Ecological Systems Theory and the Family Systems Theory. This study mixed different research methods to analyse and interpret research results obtained from a representative sample. This was achieved through the use and integration of data in the various research stages namely data collection, data analysis and discussion and reporting of findings. The qualitative data was collected and analysed to determine factors influencing the use of parenting plans during and after divorce. Qualitative data was gathered through interviews with parents who made use of a parenting plan to assist them with the transition of being an intact family to a divorced family. Interviews were conducted with 40 parents. The quantitative phase consisted of a questionnaire for a sample of 100 professionals who met the sample criteria. The questionnaire was hand delivered to the nearby respondents and emailed to the others. After the researcher explored the participants’ personal experiences, the professionals’ opinion and the literature review were completed, conclusions were drawn, and recommendations were made. The researcher concluded that all family members should be involved in drafting a parenting plan. A parenting plan assists parents in making correct choices for their children and fosters relationships between parents and children. It provides structure, eliminates conflict and protects all members included. Not all professionals who draft parenting plans have adequate training and experience. Most professionals deem that the writing of parenting plans should be a specialised field in practice. In comparing this statement with feedback from the parents who were interviewed, specialised intervention and assistance regarding parenting plans are prioritised. Guidelines for the implementation of parenting plans for parents and professionals were developed.